No Difference in 30-Day Outcome and Quality of Life in Transradial Versus Transfemoral Access - Results From the German Austrian ABSORB Registry (GABI-R). - Wein, Bastian; Zaczkiewicz, Myron; Graf, Matthias; Zimmermann, Oliver; Gori, Tommaso; Nef, Holger M.; Kastner, Johannes; Mehilli, Julinda; Richardt, Gert; Wöhrle, Jochen; Achenbach, Stephan; Riemer, Thomas; et al. (Cardiovascular Revascularization Medicine, 2022)
BACKGROUND: Radial (RA) instead of femoral access (FA) for coronary interventions has become a European Society of Cardiology Class-IA guideline recommendation. But when the decision on the access site is left to the discretion of the operator, differences in adverse event rates mitigate. METHODS: We compared the 30-day outcome for RA and FA in all patients recruited for the observational German Austrian ABSORB Registry (GABI-R) in regard to all-cause mortality, stroke, myocardial infarction (MI), TIMI major bleedings (TMB) and quality of life (QoL). All patients were treated with a bioresorbable vascular scaffold. Access site was left to the discretion of the operator. RESULTS: In total, 3137 patients included by 92 centers received percutaneous coronary interventions (PCI) for acute MI in 51.5% and non-acute settings in 48.5%. RA was performed in 47.8% and had a higher median radiation exposure (3896 vs. 3082 cGycm2, p < 0.001). There was no difference in the amount of contrast used. There was also no difference in all-cause mortality (0.53% vs. 0.49%, p = 0.86), the combination of death, MI and stroke (1.87% vs. 1.83%, p = 0.94), but a trend towards more TMB (0.47% vs. 1.04%, p = 0.07) with FA. These outcomes were consistent across the subgroups of patients with ST-elevation MI, non-ST-elevation-ACS and stable coronary artery disease. Finally, QoL did not differ between RA and FA. CONCLUSIONS: In this contemporary GABI-R cohort, in which access site was left to the discretion of the operator, both access routes were safe and equal concerning QoL (ClinicalTrials.gov; NCT02066623).
EVALuna2:482646